Situação epidemiológica da Malária no estado do Pará, 2006 a 2022 - SILVA, Benedito Rosa da (2025)
Malaria is a parasitic disease caused by a protozoan and transmitted to humans through the bite of the female anopheles darlinge mosquito. This disease is a serious public health problem, given its great impact on the mortality of the population living in endemic regions. According to data from the World Health Organization - WHO, the number of cases increased between 2020 and 2021. In Brazil, the Amazon region represents 99% of cases. Considering these factors, the research aims to analyze the epidemiological situation of malaria in the state of Pará between the years 2006 and 2022. For this, the methodology used was ecological, retrospective, documentary and quantitative approach using the secondary data collection. The data are presented as follows: incidence of malaria in Pará by mesoregion; Annual Parasitic Index (IPA) versus number of cases, incidence of malaria by type of settlement (Indigenous (IND), Garimpo (GAR), Urban (URB), Settlement (ASSENT) and Camp (ACAMP), number of cases by parasitic species and percentage of P. falciparum. After obtaining the data, graphs and tables were formulated, where it was possible to verify that: from 2006-2022, 927,875 cases were registered in the state of Pará. In this scenario, the mesoregions that presented the highest number of cases were: Marajó and Southwest, both accounting for 60% of cases. On the other hand, the mesoregion that had the lowest incidence of malaria was the Metropolitan Region with just 0.4%. The average IPA remained classified between average and low in this period, with a setback in the last year (2022), which went from low to average. The mining and settlement agglomerations were those with the highest number of cases, with 39.3% and 21% respectively and the one with the lowest number of cases was the camp with just 0.3%. It is noteworthy that there is a tendency for the incidence of the disease to increase in mining and indigenous areas, contrary to what happens in urban areas, where there is a tendency for the time series to reduce. The predominant parasitic species in Pará is P. vivax, with more than 80% of cases and the least prevalent species is P. ovale, with a percentage of just 0.001%. Furthermore, based on the logarithmic line, it was verified that there is a downward trend in the percentage of P. falciparum. Based on these data, more detailed research is suggested in the areas that present the greatest risks, considering several variables such as gender, age, level of education, social class, among others. Furthermore, it is worth emphasizing the importance of intensifying prevention measures in these areas